Analisis Pengaruh Ekuitas Merek Terhadap Minat Beli Produk Smartphone China - Hamdani, Bilal, Dr. Edy Purwo M.Si (2017)
This study describes the effect of brand equity (brand awareness, perceived quality, and brand loyalty) against China's buying interest smartphone products which data is retrieved from the Faculty of Economics and Business, University of Muhammadiyah Surakarta. In this study the authors used quantitative research, the technique of taking purposive sampling with a sample size of 100 respondents. Data obtained by spreading the questionnaire with Likert scale. The results of data analysis can be summed up as follows: first, brand awareness, perceived quality, brand loyalty individually significant effect on buying interest. second, brand awareness, perceived quality, brand loyalty is jointly have a significant influence on the buying interest, which third test results R2 of 0.274%, while the remaining 72.6% is influenced by other factors not included in this research model.